Lynn W. answered • 09/13/15

Cornell Grad For Math & CS Tutoring

We know there are two numbers, one smaller than the other. Let's call the smaller number x, and the larger number y.

Now let's translate each statement into an equation.

"One number is 4 more than another."

This means the larger number is 4 more than the smaller number. We can represent that as:

x + 4 = y

"Four times the smaller is equal to 3 times the larger increased by 1."

Since we know the smaller number is x, the left side of this equation is 4x. For the right side of the equation, we have 3y increased by 1, which is 3y+1. Putting this together:

4x = 3y + 1

Now we have a system of 2 equations to solve:

x + 4 = y

4x = 3y + 1

We can first solve for x by plugging in the first equation into the second equation:

4x = 3(x + 4) + 1

4x = 3x + 12 + 1

4x = 3x + 13

x = 13

Now we can plug x = 13 back into x + 4 = y:

(13) + 4 = y

17 = y

So the final answer is:

x = 13

y = 17

Ashley G.

09/17/15